(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
PVP proposes to be derive by PVP-Oxime(PVPO). For this reason, PVPO-TiO2 Adenine Hybrid Material produced environmental safety and all the products were divide into XRD, DLS, SEM and FTIR techniques. The result showed that the Hybrid Material supplied a value of inhibition approximately 303 K at 92 and 800 km with all material. According to AFM, absorption and AFM parameters show advanced study of units with the help of Dynamics of Molecular (MD) and Functional Theory of Density (DFT). The major limitation is when MS is in contact with these results of environments as an oxidized media it is easily collaborated with materials. Dilute Hydrochloric acid is a more beneficial and hygienic product than other Mineral acid, which is easy to handle and provides a trouble-free environment. Mineral Acid is commonly used matrix acid for many purposes. Matrix Acid helps to oxidize and use for decoration of different types of materials like iron, steel and helps to destroy many types of metal.